PERLINDUNGAN HUKUM TERHADAP TENAGA MEDIS DANKESEHATAN KETIKA BERTUGAS MENANGANI PANDEMI CORONA VIRUS DISEASE-19 DI INDONESIA - Mujahida, Nissa; Firdaus, Emilda; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Now the world is faced with a real problem, namely the Corona Virus Disease 2019 (Covid-19) pandemic. Not only the world is struggling against this pandemic, Indonesia is also entering a critical period of the Covid-19 pandemic. In this case, the front line in tackling this pandemic are medical and health personnel. However, the problem is that many medical and health workers have been exposed to Covid-19 while on duty to treat Covid-19 patients and even some of the incidents resulted in death. This incident is a big challenge in the midst of the Covid-19 pandemic considering that medical and health personnel are the main and foremost elements in handling Covid-19. The purposes of writing this thesis are: first, legal protection for medical and health personnel when in charge of handling the Corona Virus Disease-19 pandemic in Indonesia, second, the ideal concept of legal protection for medical and health personnel when in charge of handling the Corona Virus Disease-19 pandemic in Indonesia.This type of research is normative legal research that uses literature study in searching the data. This research is descriptive in nature which tries to provide detailed data on the existing problems. In writing this research using qualitative data analysis, which means explaining and concluding about the data that has been collected by the author. This research uses secondary data or scientific data that has been codified.Â The results of this study are to explain that legal protection for medical and health personnel when in charge of handling the Corona Virus Disease-19 pandemic in Indonesia has not been carried out optimally. The ideal concept of legal protection for medical and health workers when in charge of handling the Corona Virus Disease-19 pandemic in Indonesia is the first, the ideal concept according to Human Rights. In the form of fulfilling 3 aspects, namely the provision of economic protection, social protection and the provision of technical protection. These three aspects can realize the rights of medical and health workers and can also include guarantees for the protection of the rights of medical and health workers when dealing with patients during the Covid-19 pandemic. Second, the ideal concept of standard operational procedure because medical and health personnel always carry out their profession in accordance with applicable standard operating procedures.Keywords: Legal Protection - Medical and Health Workers - Corona Virus Disease-19 Pandemic